The effect of revenue growth on profitability of companies listed in the Johannesburg Stock Exchange socially responsible investing index - Sekhwela, Modjadji Crisia (My University, 2024)
Profitability of companies is a key indicator that has the potential to draw more investors and grow the economy. A high profitability increases the value of stockholder’s returns and market share price. It is therefore crucial for stockholders to uncover underlying factors that can influence profitability of companies. This study seeks to analyse the effect of revenue growth on operating profit and to evaluate the effect of revenue growth on net profit. The study utilised a descriptive quantitative method to extract secondary data from companies listed in the FTSE/JSE’s Socially Responsible Investing Index. Purposive sampling method was used to collect data from the audited annual financial statements of five (5) selected companies listed in the FTSE/JSE’s Socially Responsible Investing Index with a high market capitalisation from different categories of industries. A simple linear regression model was used to measure the correlation between independent variable which is revenue growth and dependent variables being operating and net profit. Data for each company was collected over a period of ten (10) years starting from 2011 to 2020 financial years. Companies which are not listed in the FTSE/JSE’s Socially Responsible Investing Index and those that are not contributing to Corporate Socially Responsibility were not considered in this study. The results of the study indicates that there is a correlation between independent and dependent variables. However, the results from other researchers revealed that an increase in revenue growth could give rise to a decrease in profitability if cost of sales and other operational costs associated with the generation of revenue increases. Stockholders should therefore consider identifying more variables that will determine other factors affecting profitability growth because companies that are unable to grow profitability will find it difficult to expand their operations and increase stockholders returns. Future researchers can further extend future studies to identify other variables that can influence profitability.
Thesis (MBA.) -- University of Limpopo, 2024
Keywords: Stockholders; Revenue growth; Profitability; Operating profit and net profit; Stockholders -- South Africa; Stock exchanges; Profit